A comprehensive clinical analysis of the use of percutaneous endoscopic debridement for the treatment of early lumbar epidural abscesses - Yang, Yang; Li, Jianhua; Chang, Zhengqi (Frontiers in Surgery, 2023)
The purpose of this study is to evaluate the safety and efficacy of a percutaneous endoscopic debridement and drainage for lumbar infections with early epidural abscesses.Methods: Eight cases of early epidural abscess underwent lumbar intervertebral space debridement and drainage by percutaneous endoscopic. Laboratory indicators, pathogenic microorganisms and complications were documented, and the ASIA scores were used to assess preoperative and postoperative neurological function changes.Additionally, the VAS was used to evaluate the therapeutic effect.The average duration of the drainage tube was 11.25±3.96 days (7-20 days), and the epidural abscess was eliminated after the tube was taken out. Postoperative CRP (14.40±12.50 mg/L) and ESR (48.37±16.05 mm/1 h) were significantly lower than the preoperative CRP (62.5±61.1 mg/L) and ESR (75.30±26.20 mm/1 h). The VAS score after the operation (2.50±0.92 points) was significantly lower than the one before the surgery (8.25±0.83 points). 5 patients experienced lower extremity pain and neurological dysfunction prior to surgery, however, after drainage, the lower extremity pain dissipated and the lower extremity muscle strength improved in one patient. All 8 patients were followed up for a period of (28.13±10.15) months, including 3 patients with spinal segmental instability who had lumbar bone graft and internal fixation for the second stage. At the end of the follow-up, all 8 patients were clinically cured without any progressive nerve injury, paraplegia or recurrence of infection.Percutaneous Endoscopic Debridement and Drainage is an effective way to drain intraspinal abscesses, thus avoiding any potential progressive harm to the spinal cord.